Integrasi IDEF0 Dan IDEF1 Dalam Cimosa - V. O. Lawalata (Industrial Engineering Study Program, Pattimura University, 2010)
Enterprise design that rooted from functional modeling, information modeling, and data flow diagram arranges to explain and generate the structures and operations of enterprise. Based on functional, information, resource, and organizational views CIMOSA becomes a methodology to design or redesign the enterprise. In order to integrate the importance of views the IDEF methods is use to avoid information redundancy created by each view. Especially to integrate functional view and information view IDEF0 method generates the components of view as the input to generate the logic relationship between these views by IDEF1 method. Entity become the major factor to connect the IDEF0 and IDEF1in CIMOSA.